Respons Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) terhadap Pemberian Pupuk Hayati Cair dan Pupuk Gandasil D - Hafidz Surya Kurniawan; Andi Apriany Fatmawaty; Nur Iman Muztahidin; Endang Sulistyorini (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2025)
Pakcoy (Brassica rapa L.) is a highly nutritious vegetable rich in fiber and essential vitamins beneficial for human health. The increasing consumer demand requires stable production; however, in Banten Province, productivity remains limited due to declining soil fertility caused by continuous land use. One potential solution to improve soil fertility and plant growth is through appropriate fertilization, both organic and inorganic. Liquid biofertilizer and Gandasil D are known to enhance plant growth and yield. This study aimed to determine the optimal dosages of liquid biofertilizer and Gandasil D fertilizer to achieve the best growth and yield of pakcoy. The research was conducted at Taman Alam Bareno Housing, Banjar Village, Pandeglang Regency, Banten Province, from April to June 2025, using a factorial Randomized Block Design (RBD) with two factors and three replications. The first factor was the dosage of liquid biofertilizer (H): 0 ml/L (H0), 15 ml/L (H1), 30 ml/L (H2), and 45 ml/L (H3). The second factor was the dosage of Gandasil D (G): 0 g/L (G0), 3 g/L (G1), and 6 g/L (G2), resulting in 36 experimental units. The results showed that applying 15 ml/L of liquid biofertilizer significantly increased plant height (14.68 cm) and number of leaves (6.22 leaves). Meanwhile, applying 3 g/L of Gandasil D significantly improved plant height (25.98 cm), number of leaves (14.42 leaves), fresh weight (9.95 g), and dry weight (3.03 g).